Oncogenic Ras-induced secretion of IL6 is required for tumorigenesis - Ancrile, Brooke (Cold Spring Harbor Laboratory Press, 2007)
Ras is mutated to remain in the active oncogenic state in many cancers. As Ras has proven difficult to target therapeutically, we searched for secreted, druggable proteins induced by Ras that are required for tumorigenesis. We found that Ras induces the secretion of cytokine IL6 in different cell types, and that knockdown of IL6, genetic ablation of the IL6 gene, or treatment with a neutralizing IL6 antibody retard Ras-driven tumorigenesis. IL6 appears to act in a paracrine fashion to promote angiogenesis and tumor growth. Inhibiting IL6 may therefore have therapeutic utility for treatment of cancers characterized by oncogenic Ras mutations.